Theoretical Study of Pd11Si6 Nanosheet Compounds Including Seven‐Coordinated Si Species and Its Ge Analogues. Issue 3 (10th December 2015) - Chen, Yue; Sunada, Yusuke; Nagashima, Hideo; Sakaki, Shigeyoshi
Abstract: Nanosheet compounds Pd11 (Si i Pr)2 (Si i Pr2 )4 (CN t Bu)10 (1 ) and Pd11 (Si i Pr)2 (Si i Pr2 )4 (CNMes)10 (2 ), containing two Pd7 (Si i Pr)(Si i Pr2 )2 (CNR)4 plates (R= t Bu or Mes) connected with three common Pd atoms, were investigated with DFT method. All Pd atoms are somewhat positively charged and the electron density is accumulated between the Pd and Si atoms, indicating that a charge transfer (CT) occurs from the Pd to the Si atoms of the SiMe2 and SiMe groups. Negative regions of the Laplacian of the electron density were found between the Pd and Si atoms. A model of a seven‐coordinated Si species, that is, Pd5 (Pd−SiMe), is predicted to be a stable pentagonal bipyramidal molecule. Five Pd atoms in the equatorial plane form bonding overlaps with two 3p orbitals of the Si atom. This is a new type of hypervalency. The Ge analogues have geometry and an electronic structure similar to those of the Si compounds. But their formation energies are smaller than those of the Si analogues. The use of the element Si is crucial to synthesize these nanoplate compounds. Abstract : Si is crucial : A seven‐coordinated Si atom, which interacts with Me groups, a Pd5 ring, and one more axial Pd atom in a nanosheet compound represents a new type of hypervalency (see figure). The bonding interaction of the Si atom with five Pd atoms in the equatorial plane arises from a charge transfer from the Pd5 ring to two 3p orbitals of the Si atom.